Optimalisasi Kualitas Personil Jaga Di Anjungan Agar Terjamin Keselamatan Di Atas Kapal - Aberaldo Fransisco Bakari, Aberaldo; Yosis Onasis; Santun Irawan (KALAO'S MARITIME JOURNAL, 2022)
The background of this research is the incident that occurred on a ship that experienced problems crossing with other ships in early December 2022 the MV ship, Charlotte was sailing from the loading port in Marunda (North Jakarta) to the unloading port in Palembang. At the time of the change of guard from the second officer on guard duty at 00.00-04.00 with the first mate on guard duty at 04.00-08.00, at that time the ship was in TSS towards the unloading port. In Marunda there is a tugboat that is towing a barge loaded with wood that will cut the TSS from the right side of MV Charlotte's hull. By viewing the tugboat's three parallel white lights it can be identified that the ship is less than 6 Nautical Miles away. To be sure, at that time the second mate checked through radar and it turned out that the distance from the MV Charlotte to the tugboat was 5.5 Nautical Miles. At the time of the second handover of the guard with the first mate by showing the surrounding conditions and notifying that there was a tugboat that would cut in front of the bow which was still 5.5 Nautical Miles away. Maybe because the first mate was not yet conscious because he was still sleepy, he just said "yes" to the second mate and immediately sat down in a chair without taking into account the surroundings. At that time the tugboat, whose position crossed the MV. Charlotte already saw her sidelights turning red, when the cadet checked it on the radar it turned out that the tugboat was already 3.0 Nautical Mile, so at that time the cadet immediately reported it to the first mate. At that time if one of the ships does not change course it will result in a collision hazard and the closest point indicated by the radar has shown the number zero (0). At that time the ship MV. Charlotte has communicated with the tug but there is no response and when the ships are approaching each other, where should the MV. two power-driven ships are sailing with their bows crossing each other so that there is a risk of collision, the ship which has the other ship on its starboard side must keep aside and if circumstances permit must avoid crossing ahead of the other ship”. But what happened to the first mate who had just climbed onto the bridge and was still in a sleepy state gave the order to the helmsman to change course to the left. After the helmsman observed carefully, if the ship changes course to the left, the ship will collide with the tugboat. Finally the helmsman told the first mate, that the ship would experience a collision if it changed course to the left, because the ship would meet between the bows and the tugboat. The first mate then paid close attention to the position of the ship and the tugboat, it turned out that what the helmsman had told was correct, the ship could collide with the tugboat if it changed course to the left. Finally, the first mate quickly gave an order to the helmsman for the starboard wing to take the stern of the tugboat.